Revitalization of the traditional values lost due to the commodification of art/crafts: a case study of Bataknese traditional Ulos. Issue 4 (2nd October 2019) - Zulkifli; Ridwan, Muhammad
ABSTRACT: The dynamics of modernization in Bataknese community, supported by various factors, led to the desacralization of traditions. This desacralization is due to the commodification of its cultural elements, among them the crafts of ulos. The existence of traditional ulos relates to religious life and is a manifestation of the Bataknese theology. The existence of Bataknese culture is strongly supported by the existence of ulos, which is the actualization of the 'dalihan na tolu' kinship system. Traditionally, the use of ulos in the community is governed by custom, according to the type, form, function and meaning. However, the commodification of ulos has caused inconsistencies in its development, so it is feared that this would obscure the values of tradition, which should be preserved. This paper discusses the revitalization efforts that can be conducted by the stakeholders of the craft of ulos: community, business, and government.